Major transcriptomic differences are induced by warmer temperature conditions experienced during asexual and sexual reproduction in Fragaria vesca ecotypes - Zhang, Yupeng; Viejo, Marcos; Yakovlev, Igor; Tengs, Torstein; Krokene, Paal; Hytönen, Timo; Grini, Paul E.; Fossdal, Carl Gunnar (Frontiers in Plant Science, 2023)
A major challenge for plants in a rapidly changing climate is to adapt to rising temperatures. Some plants adapt to temperature conditions by generating an epigenetic memory that can be transmitted both meiotically and mitotically. Such epigenetic memories may increase phenotypic variation to global warming and provide time for adaptation to occur through classical genetic selection. The goal of this study was to understand how warmer temperature conditions experienced during sexual and asexual reproduction affect the transcriptomes of different strawberry (Fragaria vesca) ecotypes. We let four European F. vesca ecotypes reproduce at two contrasting temperatures (18 and 28 °C), either asexually through stolon formation for several generations, or sexually by seeds (achenes). We then analyzed the transcriptome of unfolding leaves, with emphasis on differential expression of genes belonging to the epigenetic machinery. For asexually reproduced plants we found a general transcriptomic response to temperature conditions but for sexually reproduced plants we found less significant responses. We predicted several splicing isoforms for important genes (e.g. a SOC1, LHY, and SVP homolog), and found significantly more differentially presented splicing event variants following asexual vs. sexual reproduction. This difference could be due to the stochastic character of recombination during meiosis or to differential creation or erasure of epigenetic marks during embryogenesis and seed development. Strikingly, very few differentially expressed genes were shared between ecotypes, perhaps because ecotypes differ greatly both genetically and epigenetically. Genes related to the epigenetic machinery were predominantly upregulated at 28 °C during asexual reproduction but downregulated after sexual reproduction, indicating that temperature-induced change affects the epigenetic machinery differently during the two types of reproduction.